A chemometric investigation of aromatic emission profiles from a marine engine in comparison with residential wood combustion and road traffic: Implications for source apportionment inside and outside sulphur emission control areas. (October 2017) - Czech, Hendryk; Stengel, Benjamin; Adam, Thomas; Sklorz, Martin; Streibel, Thorsten; Zimmermann, Ralf
Abstract: Ship emissions are known to cause severe impacts on human health, but are less restricted than land-based emissions. A regulation to improve air quality in coastal regions and frequented waterways is the limitation of fuel sulphur content to 0.1% in sulphur emission control areas (SECAs), which has caused a switch from heavy fuel oil (HFO) towards diesel-like marine gas oil (MGO) or marine diesel oil (MDO). The fraction of aromatic organic vapours in the exhaust from a marine engine, operating on HFO and MGO, was investigated by resonance-enhanced multi-photon ionisation time-of-flight mass spectrometry (REMPI-TOFMS). MGO with fuel sulphur content (FSC) below 0.1% and HFO with an average FSC of 2.7% denote representative marine fuels inside and outside SECAs, respectively. The obtained emission spectra were combined with data of previous REMPI-TOFMS studies of combustion engines and wood combustion in statistical analyses to derive marker substances for ship emissions inside and outside SECAs. A diagnostic ratio of C2-naphthalenes to methyl-naphthalenes was found to hold for a good discriminator between ship emissions on the one hand and road traffic and wood combustion on the other hand. Furthermore, random REMPI spectra from all emission sources were mixed with different proportions in a simulation to create a model based on partial least square (PLS) regression for the prediction of ship contribution to aromatic organic vapours. We point out that in particular PAHs with higher degree of alkylation are significant markers for primary ship emissions which may support source apportionment studies inside and outside SECAs to assess the benefits of fuel sulphur content regulation on air quality. Graphical abstract: Highlights: Aromatic emission profiles of twelve real-world emission sources. Temporal variability of emissions considered. Significant aromatic markers for ship emissions in-/outside SECAs. Prediction model for contribution of ship emissions.